2011
DOI: 10.3109/13880209.2010.501456
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the possible mechanisms of antidiabetic activity of extract of aerial parts ofPhyllanthus niruri

Abstract: These findings suggest that aerial parts of P. niruri may owe their blood glucose lowering properties to inhibition of glucose absorption and enhancement of glucose storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 33 publications
2
28
0
3
Order By: Relevance
“…P. niruri was also reported to display anticarcinogenic [10], hypolipidemic [11], hepatoprotective [12], anti-inflammatory [13], and antiplasmodial [14] effects as well as an effective treatment for hemorrhagic cystitis [15]. Recent studies have also revealed antidiabetic [16] and antioxidant properties of this herbal extract [9] both in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…P. niruri was also reported to display anticarcinogenic [10], hypolipidemic [11], hepatoprotective [12], anti-inflammatory [13], and antiplasmodial [14] effects as well as an effective treatment for hemorrhagic cystitis [15]. Recent studies have also revealed antidiabetic [16] and antioxidant properties of this herbal extract [9] both in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that P. niruri possesses antiviral (20), hepatoprotective (27,30), antihyperuricemic (18), lipid-lowering (12), antimalarial (31) and antiplasmodial (19), antinociceptive (17,22), antispasmodic (13), hypoglycemic, and antidiabetic (23,24) activities.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in Asia, Africa, and South America for its vast therapeutic effects (24), Antiinflammatory effects of P. niruri aerial parts 257 to manage diabetes, constipation, fever, malaria, jaundice, hepatitis B, dysentery, gonorrhea, syphilis, tuberculosis, cough, influenza, diarrhea, vaginitis, tumors, and kidney stones (23,25,29). In Ayurveda, a decoction of the plant is administered orally for the treatment of asthma and diabetes (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although no report on P. niruri having anti-lipase activity, a few reports indirectly stated the ability of this plant as anti-obesity agent. The anti-diabetic action of P. niruri extract has been studied by many researchers [42][43][44][45]. Okoli et al [44] reported the methanolic extract of aerial parts of P. niruri showed significant blood glucose lowering and glycemic control in diabetes.…”
Section: Lipase-inhibition Of Crude Plant Extractsmentioning
confidence: 99%